PROFIL NUMBER SENSE SISWA KELAS VII SMPN MODEL TERPADU MADANI PALU DALAM MENYELESAIKAN MASALAH BILANGAN - Putu Indrayana; Sudarman Bennu (Media Eksakta, 2021)
This study aims to describe the profile of number sense of grade VII students at SMPN Model Terpadu Madani Palu in solving number problems. This type of research is qualitative research. The subject of this study were three students in grade VII CI-2 at Model Terpadu Madani Palu in the even semester of the 2020/2021. Three students selected as research subject consisted of a student with high math abilities, a student with medium math abilities and a student low math abilities. Data were collected by means of test and interview methods. The result of this study indicate that: (1) Profile of number sense of student with high mathematics ability is: (a) Representing fractions with pictures, (b) Use pictorial representations, (c) Using estimates and fraction properties to make a comparisons, (d) Using the assosiative property, (e) Understand the relationship between the problem’s context and the operation required. (2) Profile of number sense of student with moderate mathematics ability is: (a) Understand the concept of addition and substraction of fraction, (b) Using fraction properties to make a comparisons. (3) Profile of number sense of student with low mathematics ability is: (a) Able to convert fractions to decimal numbers and vice versa, (b) Understand the concept of addition and substraction of decimal numbers.